Ferromagnetic enhancement of microcrystalline cellulose via chemical reduction method - Siti Hajar, Omar; Rosli, Mohd Yunus; Khan, Maksudur R.; Mohd Mawardi, Saari (Universiti Malaysia Pahang, 2023)
Iron oxide nanoparticles (NPs) have potential in biological, biomedical, and environmental applications because of their characteristics such as magnetic susceptibility, stability and biocompatibility. However, it also has limitation, such as aggregation of magnetic NP. As a result, coating materials should be used to modify the particles’ outer surface. In this paper, we focused on the synthesis of iron oxide by chemical reduction method and coating it with Fe(III) nitrate, polyvinylpyrrolidone (PVP) and hydrazine. In order to determine effective and economical usage conditions, the coating solution at two different concentrations were prepared. The effect of coating iron oxide with microcrystalline cellulose (MCC) was prepared at different concentrations of iron (III) nitrate on the nanomaterials with respect to morphological, thermal, magnetic susceptibility. A good morphology images of FeNp-MCC were proved by Scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Energy dispersive X-ray (EDX) spectra reveals the presence of carbon, oxygen and iron in the synthesized microparticles. TGA analysis showed iron material was successfully formed into the surface of MCC. Lastly, the magnetism results proved that cellulose is strongly interacting with magnetite nanoparticles.